(untitled) (Berlin, 1989)
The scope of this series is the entire domain of marine bioorganic chemistry - ecology, pharmacology, biosynthesis, molecular structure, laboratory synthesis. Marine biologists, pharmacologists, organic and medicinal chemists will be the prime audience. The level of the reviews will be geared to researchers and graduate students in biology, chemistry and biomedicine.
Keywords: Marine ecology,Bioorganic chemistry,Marine Biology,Sinh thái học biển,Sinh vật học biển,Hóa học Bioorganic